Fe-doped NiSe2 nanorods for enhanced urea electrolysis of hydrogen generation. (1st February 2023) - Yu, Lice; Pang, Xinru; Tian, Zhiqun; Wang, Shuli; Feng, Ligang
Highlights: Urea oxidation catalyzed by NiSe2 largely improved by a facile Fe doping strategy. Doping amount of Fe would greatly impact the catalytic ability. NiSe2 with 1.68 at.% Fe-doping exhibited the best catalytic performance. Current density at 1.54 V was 4.4 times higher than that of pristine NiSe2 electrode. The cell voltage of 1.45 V to reach 10 mA cm −2 was 170 mV lower than water electrolysis. Abstract: The non-precious Ni-based catalysts are promising in the electrooxidation of urea while the low intrinsic activity still needs to be increased for practical application. Herein, we demonstrated the urea oxidation catalyzed by NiSe2 nanorod could be greatly improved by Fe doping strategy. The Fe-doping effect was probed by density functional theory which revealed that doping could enhance the interface electric field inducing the charge redistribution near the Ni atom, and enhancing the adsorption capacity of Ni to urea molecules. As a result, the balanced interaction of Fe/Ni synergism and the Ni active site exposure can be realized by tuning the Fe doped amount in the system, which would greatly impact the catalytic ability and intrinsic performance. The NiSe2 with 1.68 at.% iron doping demonstrated the highest catalytic performance for urea oxidation, displaying the largest surface-active area, highly efficient kinetics, fast charge transfer rate, and outstanding stability. The current density of 125.8 mA cm −2 for urea oxidation catalyzed by Fe doped NiSe2 electrode was obtained at 1.54 V vs. RHE when supported on the glassy carbon electrode, almost 4.4 times that of the pristine NiSe2 electrode. When constructed in the two-electrode system combined with the commercial Pt/C cathode, the cell voltage used for urea electrolysis was 1.45 V to provide the specific current density of 10 mA cm −2, approximately 170 mV lower than that of pure water electrolysis, indicating the potential application of hydrogen generation for urea-assisted water splitting. Graphical abstract: The urea oxidation catalyzed by NiSe2 nanorod can be largely improved by a facile Fe doping strategy, and the doping amount of Fe would greatly impact the catalytic ability and intrinsic performance. Image, graphical abstract